Greek Myth or Fact? The Role of Greek Houses in Alcohol and Drug Violations on American Campuses - Manu Raghav; Timothy M. Diette (Global Labor Organization (GLO), 2022)
Greek-letter student social groups, better known as fraternities and sororities, are a ubiquitous feature on many American higher education campuses. These organizations, especially fraternities, have a reputation for encouraging unruly and improper behavior among both members and non-members. This paper investigates the effect of the degree of prevalence of these Greek organizations at a campus, as measured by the percentage of students who are members of fraternities and sororities, on the instances of liquor and drug law violations on campuses, as measured by the number of arrests for liquor and drug laws violations. Using a unique dataset, which combines data from three sources, we address any potential selection bias by including several controls associated with party culture and through the inclusion of institution-level fixed effects. We find that a larger percentage of students in fraternities (but not sororities) is associated with an increase in the number of arrests for drug law violations. A larger percentage of students in sororities (but not the percentage of students in fraternities) is associated with a larger number of arrests for liquor law violations. This result is highly significant and is robust across various specifications.
Keywords: I21; K42; 330; Crimes on Higher Education Campuses; Illegal Alcohol and Drug Use; Higher Education Greek Social Organizations